2021
DOI: 10.1017/s0144686x21001367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the contribution of housing adaptations in supporting everyday life for people with dementia: a scoping review

Abstract: The primary aim of this scoping review was to explore the contribution of housing adaptations to supporting everyday life for people with dementia living at home in the community. The study adopted a scoping review methodology which was guided by the Joanna Briggs Institute Reviewers Manual. Four review questions were developed which subsequently informed the inclusion criteria and search terms. Eight databases were searched resulting in 2,339 records, with 13 papers being included in the review. Evidence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(193 reference statements)
0
3
0
Order By: Relevance
“…Illustrative of this more nuanced understanding, Nygård 17 explored life at home for people with dementia who lived alone and investigated the person's interactions with everyday objects and technologies, such as televisions, kettles, and cookers. These interactions were seen to be both creative and challenging in equal measure and where improvement in person‐centred design for people living with dementia would help to accommodate changing skills and abilities 18,19 . In addition, Newton et al's 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illustrative of this more nuanced understanding, Nygård 17 explored life at home for people with dementia who lived alone and investigated the person's interactions with everyday objects and technologies, such as televisions, kettles, and cookers. These interactions were seen to be both creative and challenging in equal measure and where improvement in person‐centred design for people living with dementia would help to accommodate changing skills and abilities 18,19 . In addition, Newton et al's 18 .…”
Section: Introductionmentioning
confidence: 99%
“…These interactions were seen to be both creative and challenging in equal measure and where improvement in person‐centred design for people living with dementia would help to accommodate changing skills and abilities. 18 , 19 In addition, Newton et al's. 18 systematic narrative review on care home and domestic gardens and the experience of living with dementia, revealed the garden as a neglected area of attention.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to demonstrate that the spatial design of care environments has a significant impact on the functional independence and overall quality of life of people with dementia (Marshall, 2001; Bowes and Dawson, 2019). Design guidance for residential care settings encourages the adoption of physical features that assist people with dementia to negotiate the physical environment, for example, lighting, decoration, fixtures and fittings, assistive technology and physical adaptations (Newton et al , 2021). Design features within care facilities can either maintain or restrict links with existing social networks, for example, through the accessibility of spaces, or through restrictions to access based on safety or security concerns (Fleming and Purandare, 2010).…”
Section: Introductionmentioning
confidence: 99%